Dry machining of T6061 aluminium alloy using titanium carbonitride (TiCN) coated tools - Mohamed Ariff, Tasnim Firdaus; Sofian, Nur Najwa; Che Mat, Nor Hayati (Trans Tech Publications, Switzerland, 2013)
In metal cutting process, the use of cutting fluids, cooling and easy chip removal causes long-term effects of cutting fluids disposal into environment. Research has also proven the health hazards on manufacturing workers who coming in direct contact with cutting fluids. Currently it is highly competitive or end-user of metal workings fluid to reduce cost and improve productivity. Considering the high cost and problems associated with health and safety, it would be desirable if the use of cutting fluids be omitted. This study investigates the flank wear behavior of coated Titanium Carbonitride (TiCN) coated tools in dry and wet machining of T6061 Aluminum alloy with the aim of obtaining the optimum cutting speed for dry and wet machining respectively. By using specific depths of cut 0.2 and 0.6 mm with feed rates of 0.4 and 0.8 mm/rev respectively, the wear was investigated for 3 different high cutting speeds; 290, 360 and 446 mm/min. Results of dry machining was compared with traditional wet machining process. The temperature of tool tip, machining time and tool wear were recorded. Wear rate of the tool increases with the increasing cutting speed and parameters for both dry and wet machining. Wear percentage difference for dry machining was found to be 21-37 % (d = 0.2 mm and f = 0.4 mm/rev) and 41 - 58% (d = 0.6 mm and f = 0.8 mm/rev) higher than wet machining. The optimum cutting speed for both cutting parameters is 446 m/min for dry and wet machining. Tool tip temperature for dry machining is found to be 14 - 16 % higher than wet machining for both cutting parameters. It is observed that dry machining is suitable for high speed intermittent cutting operations.